Examining CEFR-related professional learning interventions for language teachers: A qualitative meta-synthesis - Cameron W. Smith; Amanda Battistuzzi (Canadian Society for Studies in Education, 2023)
Current language teaching and learning reflects an increasingly situated approach, paralleling the tenets of the Common European Framework of Reference for languages (CEFR). Although these methods are promoted in language curricula globally, how language educators are being prepared to adopt these approaches is less clear. This project therefore sought to investigate how CEFR-related training interventions are being used internationally with second language (L2+) pre-service and in-service teachers. Here, we provide the results of a qualitative meta-synthesis of literature on professional learning on the CEFR. Seventeen studies met the final inclusion criteria. The existing literature demonstrates how explicit training on the CEFR can support teachers' understanding and positive perception of the framework and align teachers' planning, pedagogy, and assessment practices with contemporary tenets for language teaching and learning. These studies provide insights into the impact, opportunities, and challenges related to engaging L2 teachers in CEFR learning.